Filmer l’ambiance urbaine : Les dispositifs vidéographiques à l’œuvre chez William H. Whyte dans La vie sociale des petits espaces urbains - Laure Brayer (Ambiances)
This article examines the potential role of video in the understanding of urban environment and, particularly, in its ability to represent the urban ambiances. As part of a study regarding videographic apparatus set to work in some urban research, we are now focusing on the work of William H. Whyte and his team, and more specifically on a research entitled The Social Life of Small Urban Spaces. This research was developed from a field work centered on a videographic recording of studied spaces. We have chosen to observe videographic apparatus set up and to pay attention to ways in which they guide our understanding of a place. More than just a visual illustration, these video recordings offer clues for understanding practices, time frames and urban ambiances, specific to a place at some point.